Possible differences in effects on ejaculate morphology between shape and size components of the intromittent membranous part of insect male genitalia: Phylogenetic comparative analyses in Carabidae - Sasakawa, Kôji (Frontiers in Ecology and Evolution, 2022)
Male genitalia exhibit extreme morphological diversity among animals, but its diversification mechanism has not been fully elucidated. In insects, the intromittent membranous part has been barely studied. This study performed phylogenetic comparative analysis to examine the morphological associations between the intromittent membranous part (endophallus) and ejaculate characteristics in two Carabidae taxa with different endophallus diversification patterns (genus Amara and tribe Pterostichini). Endophallus morphology was analyzed using geometric morphometrics, whereby effects of shape and size components can be evaluated separately. In both taxa, no morphological associations were found between spermatophore and endophallus traits, but an association was detected between conjugated sperm length and endophallus shape. Considering the available information regarding functional morphology, the association between conjugated sperm length and endophallus shape may indicate a physical interaction between conjugated sperm and the endophallus through the spermatophore. The similarity of results between the two taxa implies functional equivalence among different endophallus types. Concerning individual sperm, several results were detected, but functional interpretation was difficult. Overall, these results imply that shape and size have different effects on ejaculate morphology, with a larger effect of shape than size. This pattern is consistent with previous results for non-intromittent and intromittent sclerotized parts, and the diversification mechanism of the intromittent membranous part may be similar to those of non-intromittent and intromittent sclerotized parts.